Linking peace with reconciliation: Peace on the Korean Peninsula and the Seoul–Pyongyang–Tokyo triangle. Issue 3 (8th July 2019) - Nam, Kijeong
Abstract : Purpose: The purpose of this paper is to explain Japan's role in the peace process on the Korean Peninsula that began in early 2018. Design/methodology/approach: This paper emphasizes the historical context of international politics in Northeast Asia, rather than power politics or geopolitics. The paper reaffirms the significance of the ongoing peace process on the Korean Peninsula by considering a synthesis of three joint declarations published in 1998, 2000 and 2002 between the Republic of Korea (ROK) and Japan, the ROK and Democratic People's Republic of Korea (DPRK), and between the DPRK and Japan. Findings: The normalization of diplomatic relations between DPRK and Japan, along with reaffirmation of the joint declaration between the ROK and Japan, and the Panmunjeom Declaration, would be a base for denuclearizing Northeast Asia. Originality/value: In Northeast Asia, historical reconciliation among the two Koreas and Japan and peace-building between the two parties on the Peninsula are closely linked. Moreover, the three bilateral relationships among these three parties are also the basis for creating a new multilateral security order in Northeast Asia.